The impact of using pain scales by untrained students on the decision to provide analgesia to multiple species - Oliveira, Marcela Carneiro de [UNESP]; de Lima, Mayara Travalini [UNESP]; Trindade, Pedro Henrique Esteves [UNESP]; Luna, Stelio Pacca Loureiro [UNESP] (Elsevier, 2024)
Objective: To evaluate if students without training assess pain similarly to an expert, and to compare indications for analgesic intervention based on student opinions versus scale scoring. Study design: Prospective, blind, randomized, cross-sectional study. Animals: Video recordings of a bull, horse, cat, pig and sheep. Methods: First-year veterinary medicine students assessed one video of a horse (n = 44) and one video of a bull (n = 39). Third-year veterinary medicine students assessed one video of a cat (n = 23) and one video of a pig (n = 21). Fourth-year animal science students (n = 16) assessed one video of a sheep. The species assessed by different student classes were determined randomly. Students were unaware of animal history or existing pain assessment and decided whether they would provide analgesia according to their opinion. They then scored each video using species-specific validated pain scales. Scores were compared with those of a board-certified anesthesiologist (expert). Chi-square test was used to compare students and expert. Results: Students underestimated the expert's score by 8–20%, except for the horse. There was no difference between the analgesic indication according to the assessment of the expert (143/143, 100%) and students (141/143, 98.6%) considering the defined analgesic intervention threshold for each scale (p = 0.478). The indication for analgesic intervention according to students’ opinion (116/143, 81.1%) was lower than that according to their scale scores (141/143, 98.6%) (p < 0.0001). Conclusions and clinical relevance: Students tended to underestimate pain; however, they detected pain that requires analgesic intervention in animals similarly to an expert. The use of scales optimized the indication for providing analgesia when animals were experiencing pain that required analgesic intervention.
Keywords: acute postoperative pain; analgesia; animal welfare; pain measurement; postoperative care